2019
DOI: 10.1016/j.conbuildmat.2018.11.099
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage properties of plain and recycled steel–fibre-reinforced rapid hardening mortars for repairs

Abstract: Non-uniform drying of rapid hardening overlays can lead to cracking and delamination. • Mixes with CSA cement showed much lower shrinkage strains than mixes with RSC cement. • RSC and FRSC mixes showed considerable autogenous shrinkage at the age of 60 days. • FE analysis were used to predict shrinkage development using hygral contraction coefficient. • Creep plays an important role in moderating stresses of overlays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…about 18.8% lower than that of F0. This finding is consistent with Al-musawi et al (2019) that RTSF with high tensile strength can bridge the crack induced by shrinkage, which transfers the stress leading to the enhancement in tensile strength. Regarding the hybrid fibre combination, increasing the PPF content did not induce a consistent trend in reducing the drying shrinkage.…”
Section: Drying Shrinkagesupporting
confidence: 91%
“…about 18.8% lower than that of F0. This finding is consistent with Al-musawi et al (2019) that RTSF with high tensile strength can bridge the crack induced by shrinkage, which transfers the stress leading to the enhancement in tensile strength. Regarding the hybrid fibre combination, increasing the PPF content did not induce a consistent trend in reducing the drying shrinkage.…”
Section: Drying Shrinkagesupporting
confidence: 91%
“…Besides the geometric properties, the purity of recycled tyre steel fibres also plays a crucial role in the effective reinforcement of cement composites with RTSFs. As supported by numerous scientific papers [ 15 , 24 , 26 , 34 , 35 , 36 , 37 , 38 , 39 ], rubber and textile contaminants present in untreated tyre steel fibres have a deteriorating effect on reinforcement effectiveness by, for example, creating a continuous barrier on the fibre surface, reducing the adhesion of the fibres to the cement matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effects of various types of tyre fibres and their mixture with manufactured steel fibres on the rheological and mechanical properties of concrete [ 26 , 34 , 35 , 36 ] indicate that, due to the presence of rubber and textile contaminants and steel dust, higher amounts of the steel cord obtained from tyres should be added compared to manufactured steel fibres. The most commonly used and financially viable tyre recycling methods involve a combination of mechanical shredding and granulation to produce steel fibres with irregular shapes, lengths, and diameters.…”
Section: Introductionmentioning
confidence: 99%
“…In some papers, the RSF content of mortars is referenced for concluding the optimized content of RSF for concrete. For example, Liew and Akbar [ 12 ] and Ahmed et al [ 31 ] reported that the research carried out by [ 32 ] showed that 45 kg/m 3 of RSF increased the compressive strength of the concrete. However, research by the authors [ 32 ] was related to the impact of RSF on cement mortars, not concrete.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liew and Akbar [ 12 ] and Ahmed et al [ 31 ] reported that the research carried out by [ 32 ] showed that 45 kg/m 3 of RSF increased the compressive strength of the concrete. However, research by the authors [ 32 ] was related to the impact of RSF on cement mortars, not concrete. Similarly, the research of [ 33 ] was related to incorporating RSF in mortars, and [ 12 ] reported it as concrete.…”
Section: Introductionmentioning
confidence: 99%